Pendampingan Pemberdayaan Potensi Masyarakat dalam Bidang Pertanian dan Home Industry di Desa Butuh Kras Kediri pada Masa Pandemi Covid-19 - Umi Khoirun Nisa’; Khoirotul Izzah (LP3M IAIFA Kediri, 2020)
Local potential is the wealth of Islam, culture, and human resources in an area. The potential of nature in a region depends on the geographical conditions, climate and landscape of the area. In this report entitled